Evaluating Curative Effects of Different Moxibustion Temperatures on Patients with Spastic Hemiplegia after Stroke - Liu YANG; Haili MA; Li GE; Qiaojing LIAO; Qiong HAN; Ling YE (康复学报)
Objective:To evaluate therapeutic effects of different moxibustion temperatures on stroke patients with spastic hemiplegia, in order to provid suitable and objective moxibustion temperature for such patients with abnormal perceptual abnormalities.Methods:A total of 80 patients were randomly divided into thermal burning group and temperature-sensing group, with 40 cases in each group. The thermal burning group received moxibustion at 36.8-43.5℃ and the temperature-sensing group received moxibustion at 32.8-35.8℃, 30 minutes each course, one course a day and five courses a week, continuous treatment for four weeks. A modified MAS scale was used to assess the degree of spasticity; a simplified Fugl-Meyer scale was used to assess motor function; Barthel's number was used to assess the ability of daily living.Results:Comparing the difference at the end of intervention to that before, the degree of upper limb paralysis was improved in both groups with statistically significant difference (P<0.05), the effect of thermal burning group improved more obvious. Comparison of two groups showed that the major effects of time were statistically different (P<0.05), but the major effects of intervention with no significant different (P>0.05).After four treatments, two groups of motor function, daily life ability were greater than the corresponding minimum clinically important difference, with statistical significance (P<0.05), thermal burning groups was more obvious.Conclusion:Different moxibustion temperature has a certain therapeutic effect on limb paralysis in patients with stroke, which can improve physical paralysis effectively, improve motor function and daily life ability, the thermal burning group is superior to the temperature-sensing group, and with low incidence of adverse events is low.